An Analysis of Syntactic Complexity in Texts Translated by Google Translate and Human Translator from Arabic into English - عزيز محمد عبده سعيد (الآداب للدراسات اللغوية والأدبية)
This paper compared the syntactic complexity of translations from Arabic into English produced by Google Translate with human translation of the same texts using the web-based L2 Syntactic Complexity Analyzer (L2SCA). Syntactic complexity is an important aspect of writing quality and language proficiency in general. Understanding how machine translation tools deal with syntactic complexity when translating texts from Arabic into English will offer insights for their efficacy. The study analyzed the syntactic complexity of translations of five text samples collected from an Arabic book “Hiwar Ma’a Sadeeqi Almulhid” [Dialogue with An Atheist] by Mostafa Mahmoud. The output of Google Translate is compared with human translation for the same texts by Mohammed Yahia. The results showed that Google Translate output has lower syntactic complexity ratios for most of the 10 indices measured. The paper highlighted key findings that have implications for developing machine translation quality. This paper contributes to the ongoing development of machine translation.